Vulnerability of the European air transport network to major airport closures from the perspective of passenger delays: Ranking the most critical airports - Voltes-Dorta, Augusto; Rodríguez-Déniz, Héctor; Suau-Sanchez, Pere (Elsevier, 2017)
This paper analyzes the vulnerability of the European air transport network to major airport closures from the perspective of the delays imposed to disrupted airline passengers. Using an MIDT dataset on passenger itineraries flown during February 2013, full-day individual closures of the 25 busiest European airports are simulated and disrupted passengers then relocated to minimum-delay itineraries. Aggregate delays are used to rank the criticality of each airport to the network, with the possibility of disaggregating the impact across geographical markets. The results provide useful reference values for the development of policies aimed at improving the resilience of air transport networks.
Keywords: Air transport networks; Resilience; Criticality; Passenger recovery